2021
DOI: 10.1007/s40336-021-00469-2
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of positron emission tomography in the evaluation of renal health and disease

Abstract: Purpose Positron emission tomography (PET) is a nuclear imaging technique that uses radiotracers to visualize metabolic processes of interest across different organs, to diagnose and manage diseases, and monitor therapeutic response. This systematic review aimed to characterize the value of PET for the assessment of renal metabolism and function in subjects with non-oncological metabolic disorders. Methods This review was conducted and reported in accordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Positron emission tomography (PET) represents the current gold standard for the assessment of tissue metabolic rates in humans in vivo. [ 18 F]FDG is the most widely used PET tracer assessing glucose uptake rates [ 69 ], but there are several other tracers that can be used for assessing different aspects of metabolism and perfusion [ 70 , 71 , 72 ]. The various PET tracers used in the study of renal function have recently been reviewed elsewhere [ 72 ].…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET) represents the current gold standard for the assessment of tissue metabolic rates in humans in vivo. [ 18 F]FDG is the most widely used PET tracer assessing glucose uptake rates [ 69 ], but there are several other tracers that can be used for assessing different aspects of metabolism and perfusion [ 70 , 71 , 72 ]. The various PET tracers used in the study of renal function have recently been reviewed elsewhere [ 72 ].…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…[ 18 F]FDG is the most widely used PET tracer assessing glucose uptake rates [ 69 ], but there are several other tracers that can be used for assessing different aspects of metabolism and perfusion [ 70 , 71 , 72 ]. The various PET tracers used in the study of renal function have recently been reviewed elsewhere [ 72 ]. From a metabolic perspective, in a renal 14(R,S)-[18F]Fluoro-6-thia-heptadecanoic acid ([ 18 F]FTHA) PET study, we showed that renal free fatty acid (FFA) uptake was higher in patients with obesity compared to lean individuals and that six months following bariatric surgery renal FFA uptake was still high (and not normalized) because of the ongoing catabolic state [ 73 ].…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Positron emission tomography (PET), widely applied for metabolic examinations in the brain, heart, and other tissues, is more difficult to apply for renal metabolism, in part arising from the accumulation of PET tracers in urine. 13,14 Nevertheless, a number of PET tracers have been evaluated for imaging kidney metabolism. These include 11 C-acetate, 15 O-water, and 18 F-6-thia-heptadecanoic acid ( 18 F-FTHA) for measuring renal oxidative metabolism, 15 oxygen consumption, 16 and free fatty acid uptake, 17 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed understanding of intermediary metabolism in the kidneys in vivo is an important goal. Positron emission tomography (PET), widely applied for metabolic examinations in the brain, heart, and other tissues, is more difficult to apply for renal metabolism, in part arising from the accumulation of PET tracers in urine 13,14 . Nevertheless, a number of PET tracers have been evaluated for imaging kidney metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, I read with interest the systematic review by Amoabeng et al that was published in recent issue of Clinical and Translational Imaging [1]. This article reviewed the utilization of positron emission tomography (PET) studies in the evaluation of renal health and diseases.…”
mentioning
confidence: 99%